A Descriptive Study On Bilingual Method In Teaching Biology At The Seventh Grade Of SBI Class In SMP N 1 Boyolali In 2011/2012 - Puspitaningsih, Dwi Jayanti Novi; , Drs. Djoko Srijono, M. Hum; , Aryati Pasetyarini, M.Pd (2013)
The research aims at describing the application of bilingual method in teaching-learning process at seventh grade of SMP N 1 Boyolali as International Standard School in 2011/2012 academic year. It is conducted to describe the implementation of teaching-learning process of Biology by using Bilingual method at SMP N 1 Boyolali and the problems faced by teacher in teaching Biology by using Bilingual method. The object of the study is the teaching-learning process on Biology at seventh grade of SMP N 1 Boyolali as International Standard School in 2011/2012 academic year. The subject of the study is the Biology teacher and the students at seventh grader in SBI class at SMP N 1 Boyolali in 2011/2012 academic year. The method of collecting data are observation, interview, and document analysis. In analyzing data the writer applied descriptive qualitative research consisting of data reduction, data display, and drawing conclusion. The result of the study shows that the model of teaching-learning activities on Biology of SBI class uses Bilingual method. Then, the syllabus and the lesson plan are designed in English. Furthermore, in teaching Biology, teacher delivers and explains the material to the students 30% in English and 70% in Indonesian. In addition, the teacher acts as facilitator, material designer, and motivator. Then, the students roles are as active learner and listener. The problems faced by the teacher are the limited capability of the teacher, the students do not understand when the teacher uses English, and the complexity of the materials.